(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1996)
Reports excavations in the course of conservation work that revealed the church’s structural evolution. Medieval and post-medieval burials were discovered along with indications of pre-church activity. There are details of `Coins and coin-weight’ by N M McQ Holmes (898–9).